Genetical and Biochemical Study in Duchenne muscular dystropy ca rriers - Ibrahim, H. I.; Hasson, A.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Six  females definite Duchennc  carriers  and 8 females of possible carriers were examine  in this study  by serum  C.P.K after exercise and muscle  Biopsy for histochemical  study. This st udy was compared with that of normal  person.The   scnm1 C.P.K   was  found   to  be  highly  elevated   in  all  the   14catTiers,   while   slight   -  moderate   elevation   was  found   in  normal control.All the definite carriers and 6 ex pected gave abnormal  histochemistry in their muscles. the other 2 gave no definite abnormality.So these  tests can be used  in  the (uturc  for assessment of  Duchenne carriers.